Risks as an object of internal control: identification and assessment - М.М.; I.I. (Економіка, управління та адміністрування)
Identification and assessment of business risk, determining the level of its materiality and impact on the functioning of economic entities of various organizational and legal forms and forms of ownership, is possible with a properly organized system of internal control. The main purpose of internal control is to ensure timely detection and analysis of business risk, reliability of relevant information, integrity of assets, compliance with regulations, internal policies and procedures, implementation of plans and efficient use of resources. The peculiarities of the methodological tools of internal control of risk detection and assessment in accordance with the nature and structure of business processes are determined, on the basis of which the content of indicators is formed: the probability of risks and the magnitude of possible losses. It is established that business risk should be considered as an integrated risk, which should objectively take into account three main categories of risk – credit, operational and market risk (liquidity risk), which will cover not only the financial and economic aspects of business entities, but also social and environmental. Based on data modeling of the accounting system with simultaneous comparison of production balances, which reflect the structure and aspects of various economic processes of the enterprise, accounting and analytical support of internal control of economic and environmental risk is proposed, taking into account three types of risks and the level of internal control. Such provision is universal and will allow to some extent to feel the impact of aggregate entrepreneurial risk, and based on the mobilization of internal and external resources, to create and regulate the internal control of the enterprise reserve system as the main tool to neutralize the level and degree of aggregate entrepreneurial risk.